FEATURES OF PUMPKIN AND SQUASH GROWING FOR MECHANICAL SEPARATION OF SEEDS - L. V. Pavlov; N. S. Tsiganok; P. N. Tokarev; E. A. Vasiliev (Овощи России)
The features of growing of pumpkin and squash for seed production in the conditions of the Moscow region are shown. The size-weight characteristics of grown fruits and seeds of pumpkin crops in order to use these indicators in machine seeds selection are shown.